Mark Twain's undictionarial Italian: the politics and visual humor of mistranslating newspaper scraps, c.1900. Issue 3 (3rd July 2022) - Greenhill, Jennifer A.
Abstract: Can a writer be considered a visual humorist? If words are the writer's primary material, can they be bent into caricatural or grotesque formations? Through what filters must words be processed or mediated for comic pictures to emerge? This article seeks to answer these questions by focusing on an understudied short story that Mark Twain wrote in Florence, Italy: "Italian Without a Master, " published in Harper's Weekly in 1904. The story offers a wild ride through the Italian language from the perspective of an English-speaking narrator who espouses "undictionarial" methods of translating the words he finds in the daily newspaper. To encourage readers to look at words with fresh eyes, Twain supplied, as his illustrations, clippings cut from the Italian papers. With these word-filled illustrations, Twain tests an expanded and experimental visuality, I argue, while also reimagining the terms of visual caricature. The story thus announces the capaciousness and elasticity of the writer's comic vision, demonstrating his mastery over multiple domains. At the same time, however, the story also criticizes the impulse to expand into new territory by subtly gesturing to the geopolitics of imperialist "mastery, " which Twain railed against repeatedly at the turn of the century.